MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN SOSIOLOGI POKOK BAHASAN KELOMPOK SOSIAL MELALUI MODEL PEMBELAJARAN STAD DI KELAS XI II SMA NEGERI 3 KUALA KAPUAS - Reny Herlina (JURNAL SOCIUS, 2015)
Based on the observation result of the researcher who is also the teacher of Sociology at the school, there were some weaknesses of students in understanding the lesson namely: (1) lack of enthusiasm; (2) lack of attention at the lesson; (3) feeling shy to ask about the lesson is not understood; (4) inactive involvement of the students on the teaching and learning process and boredom tendency; (5) lack of doing the practice tests. This observation had been supported by the findings that 77% students whose score was under the Minimum Standard Score (KKM) out of 28 students. Only 33% students met the criteria of the Minimum Standard Score (KKM). From the results of this preliminary study, researcher felt the need to make approach change in the teaching and learning process. The objectives of this research were: (1) to increase the students’ motivation; (2) to improve the students’ achievement on Sociology on the topics of Social Group through Students Teams Achievement Division (STAD) Model; (3) to find out the student’s responses on the STAD model. The research method applied was the qualitative one and to overcome the teaching and learning problems is by STAD model. The technique of data collection was observation. As the result, good responses from the students towards this STAD model can be seen from the enthusiasm of the students in following the lessons and the questionnaire results which also showed that 42,86% of students who strongly agreed, and 0% of them who disagreed on the use of STAD model. To increasing the students motivation, a teacher is recommended to apply the STAD model because this model has been tested and researched by several teachers in several different schools, and is has been proven successful in increasing the students motivation and achievement.Key words: Motivation, Study Achievement, STAD Model